Physicochemical study of absorption of CO2 into electric arc furnace slag - Muhd Nor, Nik Hisyamudin (2011)
Increase in the COz concentration in atmosphere due to the combustion of fossil fuels has caused serious global warming. In dealing with this issue, the absorption of COz into EAF steelmaking slag was experimentally studied by the utilization of mechanical grinding method. The final objective of this research is to develop a new mineral carbonation process that has a high efficiency in the capture and storage of C02 with low energy consumption and at the same time has some value added features that leads to the feasibility of the overall carbonation system. In the first stage of this study, the absorption behavior of C02 into metal powders and CaO contained material was studied by dry grinding in a centrifugal ball mill. It was found that COz was not decomposed during the grinding, but the sorption of it occurred on the ground sample. In both cases of CaO and waste concrete, formation of CaC03 was confirmed. While, in the case of metal powders, the COz absorption into ground powders was firstly occurred, thereafter, it decomposed to form metal oxides and carbon. COz sorption into the samples depended on the newly exposed surface area that was formed by grinding. It was found that the newly exposed surface area increased linearly with the increase in the grinding time. However, the dry grinding resulted to the agglomeration of particles in the latter stage of grinding. The agglomeration of particles has then led to the limitation of the COz absorption. In the next stage, the behavior of C02 absorption into EAF normal and stainless steel reducing slag was investigated with wet grinding method. The slag was wet ground under COz atmosphere by a vibrating ball mill which has larger capacity than the centrifugal ball mill. The amount and the initial rate of C02 absorption for the wet grinding were higher than those for the dry grinding. The optimum ratio of fillings to vessel's volume was found to be aboct 112. C02 was stored into the slag mainly as CaC03 and EO desorption of C02 was observed. Thus, this indicates that the C02 can be stored permanently inside the slag with this method. This study also revealed that the increase in the interfacial area between COz and the slurry of water and slag was necessary to enhance COz absorption. It was found that the absorption capacity of C02 into the normal and stainless steel reducing slag using this method on the most optimum grinding condition was 0.21 and 0.3 1 kg CO~lkg slag respectively. To profoundly investigate the mechanism of COz absorption, study on the absorption behavior of C02 into EAF normal and stainless steel oxidizing slag with wet grinding method was also conducted. The results showed that the conversion ratio of CaO to CaC03 was not solely affected by the CaO content in the slag, but by the CaO/A1203 ratio in the slag. The conversion ratio linearly increased with the increase in the Ca01A1203 ratio. The rate of CO2 absorption in the slag with wet grinding method was highly depended on the dissolution behavior of ca2+ ion from the slag into water and the interfacial area between the COz gas and water. The rate increased with the increase in the both factors. The dissolution behavior of 2+ . Ca d~ffered between each slags depended on the main phases reaction in the slag. Thus, the main phases in each slags affected the overall reaction of the C02 absorption. The 2Ca0.A1203.Si02 was found to hinder the absorption of CO2 into the slag. While CaO.Si02 and 2Ca0.Si02 phases in the slag were favorable for the CO2 absorption. It was found that the absorption quantity of CO2 into the stainless steel oxidizing slag with low A1203 content on the most optimum grinding condition was about 0.26 kg CO&g slag. Comparison between the amount of C02 absorption in this study and the amount of CO2 emitted from various power plants, which was estimated by the energy consumption of the vibrating mill, revealed that the former was not always higher than the latter. Reduction amount of 1% from overall C02 emission from steel industry can be expected by this method. Use of other possible materials will lead to the increase in the potential reduction amount. The overall cost for the system is expected to be very low and this also indicates that this method is economically feasible. Along with the absorption of C02, Zn could be removed by using this method with high removal ratio. The dissolutions of Cr were low for all conditions and the pH of the sluny were within the environmental quality standard. It was also found that even though the mortar made from the ground carbonated slag can't be used to concrete, however, it can still be used as normal mortar.